Proximal iliotibial band thickness as a cause for recalcitrant greater trochanteric pain syndrome. Issue 3 (8th August 2018) - Khoury, Anthony N; Brooke, Karina; Helal, Asad; Bishop, Benton; Erickson, Lane; Palmer, Ian James; Martin, Hal David
ABSTRACT: To investigate iliotibial band (ITB) diameter thickness at the greater trochanter in patients requiring iliotibial band release who have failed conservative modalities, in comparison to an asymptomatic patient population. A total of 68 subjects were selected to be reviewed using T2 axial plane MRI. The ITB diameter thickness was measured in 34 subjects who underwent surgical ITB release, and compared with a match-paired asymptomatic hip cohort consisting of 34 subjects. ITB diameter thickness was measured at the thickest location for each subject twice by two different examiners. Inter/intra class correlation coefficient was determined for ITB measurement technique accuracy, and the presence of recalcitrant proximal hip pain was evaluated. Interclass correlation coefficient with 95% confidence was measured to be 0.953. The average thickness for ITB surgical release subjects was measured to be 5.61 ± 2.10 mm, and for asymptomatic subjects 3.77 ± 0.79 mm ( P  < 0.001). The results of this study demonstrate a statistically significant positive relationship of an increased diameter thickness in the ITB in symptomatic patients who failed conservative therapy and underwent surgical intervention for treatment.